Potential of Sago For Commercial Production Of Sugars - Kopli, Bujang (Universiti Malaysia Sarawak, UNIMAS, 2011)
This presentation reviews previous research works and publications, and regales the accumulated knowledge on the conversion of sago starch and sago hampas into sago sugar. Previous works have focused on the fermentation of this sugar into either lactic acid or bioethanol under various parameters and approximation for commercial scale process. This report however, details on the renewed interest into a very much lower capital and less technical process of producing sago sugars (liquid and crystallised). It also befits the level of technology widely available in absence of huge capitals to initiate the project at pre-commercial level. Sago starch can be enzymatically hydrolysed into sugar with total (100%) recovery and the syrup purified using powdered activated charcoal to remove all impurities and colour. Scaling up the process (up to 10kg) did not significantly reduce the sugar recovery during hydrolysis. Apart from sago starch, lab-scale hydrolysis of treated sago hampas can generate up to 40 to 80% sugar, which not only will create extra income for the sago mill operators, but will concomitantly reduce environmental pollution frequently associated with the sago industries. Sago sugar contains mostly glucose (94%), with maltose and other impurities, both at 3% each. Drying of the purified sago syrup is best performed using an oven (minimum 60oC), producing high (100%) recovery albeit after several days. Analysis of sweetness revealed that the purified sago sugar is as sweet as 50% glucose. Sago starch therefore has a potential to be the alternative raw material to complement the frequent shortages of sugar supplied by processing imported sugar cane in this country.